مساهمة رجال البيع في بناء الصورة الذهنية للمصارف الإسلامية، دراسة تطبيقية لعملاء بنك البركة الجزائري - وكالة باتنة -. - عبد العزيز, خالد; بولحية, الطيب (khazzartech الاقتصاد الصناعي, 2021)
تهدف هذه الدراسة إلى التعرف على دور البيع الشخصي في بناء الصورة الذهنية للمصارف الإسلامية، وذلك من خلال دراسة أثر مهارات رجال البيع على أبعاد الصورة الذهنية المدركة لدى العملاء. ولتحقيق ذلك أجريت دراسة ميدانية تبعا للمنهج الوصفي التحليلي على عينة من عملاء فرع مصرف البركة الجزائري بولاية باتنة، والتي توصلت إلى وجود أثر لمهارات رجال البيع على جميع أبعاد الصورة الذهنية المدركة لدى العملاء، وخاصة على البعد المعرفي، في حين كانت أهم التوصيات هي ضرورة الإهتمام بتكوين رجال البيع وتنمية مهاراتهم بالتدريب. The present study aims to identify the role of personal selling in building the mental image of Islamic banks, through studying the effect of banking salesmen skills on dimensions of clients’ perceived mental. To achieve that, a field study was conducted following the descriptive-analytical method on a sample of clients of the Algerian Al Baraka Bank branch of Batna, which concluded to the presence of an effect of salesmen's skills on all the dimensions of clients’ perceived mental image especially on the cognitive one, while the most important recommendations were the training personal selling and developing their skills.